My arm is a branch. The ecology of mind between body extension and interweaving with the world - Lampredi, Giacomo (Scenari, 2021)
This article has the vocation of being a small place in which we can dialogue about the relationship between the enactive approch to cognition and the ecological humanism. The enactive approach underlines how the organisms create their own perceived world and interpret it. World and organism in this sense specify each other forming a new unit. The environment (even his organic components) is as important as the subject in determining experiences and ideas, because there would not be the phenomenon of perception without something to be perceived. The purpose of this article is to analyze how the natural world is influent in the formulation of experiences, memories that are transformed into artistic ideas that in turn are bound in their realization from the dependence to that natural world that has helped to generate them.